2000
DOI: 10.2139/ssrn.1808064
|View full text |Cite
|
Sign up to set email alerts
|

Now You See it, Now You Don't: Why Do Real Estate Agents Withhold Available Houses from Black Customers?

Abstract: Potential home buyers may initiate contact with a real estate agent by asking to see a particular advertised house. This paper asks whether an agent's response to such a request depends on the race of the potential buyer or on whether the house is located in an integrated neighborhood. We build on previous research about the causes of discrimination in housing by using data from fair housing audits, a matched-pair technique for comparing the treatment of equllay qualified black and white home buyers. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 30 publications
3
74
2
Order By: Relevance
“…9 There appears to be no association between neighbourhood segregation and discrimination against ethnic minorities. Contrary to previous research in the U.S. (Hanson and Hawley 2011;Ondrich et al 2003;Page 1995), ethnic minorities do not run a greater risk of being discriminated against in neighbourhoods with fewer ethnic minorities. In the U.S., ethnic discrimination in the housing market may be due to lessors trying to prevent neighbourhoods crossing the tipping point (Hanson and Hawley 2011); this is not the case here.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…9 There appears to be no association between neighbourhood segregation and discrimination against ethnic minorities. Contrary to previous research in the U.S. (Hanson and Hawley 2011;Ondrich et al 2003;Page 1995), ethnic minorities do not run a greater risk of being discriminated against in neighbourhoods with fewer ethnic minorities. In the U.S., ethnic discrimination in the housing market may be due to lessors trying to prevent neighbourhoods crossing the tipping point (Hanson and Hawley 2011); this is not the case here.…”
Section: Resultscontrasting
confidence: 99%
“…A tendency towards this process is apparent in the US, where real estate agents steer black candidate-buyers towards lower priced properties (Ondrich, Ross, and Yinger 2003).…”
Section: Therefore We Expect That Better Language Proficiency Is Assmentioning
confidence: 99%
“…Second, discrimination could push blacks and Hispanics into neighborhoods with poor amenities, thereby reinforcing the correlation between unobserved neighborhood traits and ethnicity discussed above. One study based on 1989 housing audit data (Ondrich, Ross, and Yinger 2003) found that even after controlling for housing price, real estate brokers steered blacks, but not whites, toward neighborhoods that had lower average house values or higher average house ages than the one that was original requested. Third, discrimination might restrict the ability of minority households to move out of largely minority neighborhoods and thereby artificially boost housing prices there.…”
Section: Neighborhood Ethnic Compositionmentioning
confidence: 99%
“…In this respect, housing market discrimination has been shown to play a central role in the segregation of Blacks, as evidenced by real estate agents who propose Black customers make fewer visits than White customers (Yinger, 1986). Such a discriminating behaviour finds two direct explanations: sheer racial discrimination (Becker, 1971) where suburban homeowners do not wish to sell or rent to Blacks; and, customer discrimination where real estate agents want to avoid Blacks settling in neighbourhoods that they think would then become less attractive for their White customers (see Ondrich et al, 2001). Housing market discrimination can also be accounted for by statistical discrimination in the context of imperfect information (Phelps, 1972;Aigner and Cain, 1977) where Blacks are perceived, on average, as bearing a higher default risk.…”
mentioning
confidence: 99%